Digital Circuit Design Using Dynamic Fitness Functions - Reis, Cecília (2019)
This paper proposes and analyses the performance of a Genetic Algorithm using two new concepts, namely a static fitness function including a discontinuity measure and a fractional-order dynamic fitness function, for the synthesis of combinational logic circuits. In both cases, experiments reveal superior results in terms of speed and convergence to achieve a solution.